Russia's new military doctrine: NATO, the United States and the "colour revolutions" - Margarete Klein (Stiftung Wissenschaft und Politik (SWP), 2015)
Russia's new Military Doctrine is characterised by its close linkage of foreign and domestic threat perceptions. While the former relate to NATO and the United States, the Kremlin's concerns over the latter revolve around the spectre of a Russian "Maidan". To prevent that, and to assert its claims to a zone of influence in the post-Soviet space, Moscow is in particular expanding its "non-linear" warfare capabilities. This is precisely the point to which the West has to date failed to find an adequate response. (SWP Comments)
Keywords: 320